SOSIALISASI KEAMANAN DIGITAL UNTUK PERLINDUNGAN DATA PRIBADI SISWA SMA SUMPAH PEMUDA JAKARTA - Fitri Nurlaela; Yeskarwani Gulo; Okky Prasetia (Universitas Pamulang, 2026)
The rapid development of information technology has driven the increasing use of digital devices among adolescents, particularly high school students. However, this high level of technology use is not matched by adequate digital security literacy, leaving students vulnerable to misuse of personal data, online fraud, and various other cyber threats. This Community Service activity, conducted at Sumpah Pemuda High School, aimed to increase students' understanding, awareness, and practical skills in maintaining digital security and protecting personal data through interactive outreach, case study discussions, and practical account security simulations. The methods used included material counseling, solving real-life cases related to cyber threats, and hands-on practice such as creating strong passwords, setting social media privacy settings, and activating two-factor authentication. Evaluation was conducted through pre- and post-tests, practical observations, and participant satisfaction questionnaires. The results of the activity showed a significant increase in students' knowledge of basic digital security concepts, changes in attitudes toward wiser and more responsible social media use, and their ability to independently implement account security measures. This activity contributes to fostering a culture of digital literacy within the school environment and fostering a younger generation that is more aware, critical, and resilient in the face of cyber risks. Furthermore, outputs such as modules, video documentation, published articles, and student commitment declarations are part of ongoing efforts to strengthen the digital security ecosystem in schools. Thus, this program has a tangible impact on improving students' digital skills and can be replicated at other partner schools. Keywords: Digital security, digital literacy, personal data protection, high school students, outreach.